Folk and Apocryphal Motives of The Nativity Cycle, Reflected in Cyrillic Manuscripts from Ugľa Monastery from the 17th Century - Шашерина, Светлана (Studia Ceranea, 2014)
This paper deals with Apocryphas of the nativity cycle, particularly motives of the Three Wise Men arriving, which includes Afroditian’s legend as well, in cultural context of Transcarpatia, which is a border area between Slavia latina and Slavia byzantina. The datas for study were two cyrillic manuscripts from Ugľa monastery from the 17th century.